An overview of climate-driven stress responses in striped catfish (Pangasianodon hypophthalmus) – prospects in aquaculture - Zannat, Md Meftahul; Hossain, Farzana; Rahman, Umme Ohida; Rohani, Md Fazle; Shahjahan, Md (Asian Journal of Medical and Biological Research, 2023)
Aquaculture sector significantly contribute in terms of food and nutrition security, sustainable livelihood, poverty eradication as well as overall economic development throughout the world. However, sustainable aquaculture production is a great challenge due to the climate change issues including global warming, rainfall variation, flood, and salinity intrusion. To consider the negative effects of climate changes on aquaculture production, culture of striped catfish can be one of the effective strategies for adaptation to climate changes. The capability to tolerate several adverse environmental conditions makes it a suitable aquaculture species. Moreover, striped catfish can be cultured at high stocking densities in wide range of waterbodies such freshwater, brackish water and saltwater environment as well as culture practices including monoculture, polyculture, and cage culture. Finally, it is highly recommended that striped catfish could be the best suitable candidate for aquaculture to adapt the future climate changes. Asian J. Med. Biol. Res. 2023, 9 (3), 70-88